(3Gdcajd HeYGfj GdJfRjds - (3CHh GdMSjf Hf CHj HcQ Hf GdMSjf, YeGO GdOjf GdcfOj,J (B741 (3g` s
(3ChdgG (B:s
(3JaSjQ bhdg JYGdi (B:" (3cd faS HeG cSHJ QgjfI(B" (3ef ShQI GdoeOKQ s
(3BNQgG (B:s
(3ShQI GdeSO s
(3GdfSNI HgG MhGTs
(3ocJHJ aj MjGI GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B316s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B41 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B32 - (3U (B1502s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs